Perancangan Sistem Informasi Pembukuan UKM Konveksi Bim Collection Berbasis Website Dengan Metode OOAD - Rahmawati, Diah; Gufran, Muhamad Raihan; Komalasari, Nia (Universitas Islam Syekh Yusuf, 2022)
The development of the internet in the world of technology has brought major changes to the business world, especially with the presence of websites. Websites play an important role in the effectiveness of financial management and bookkeeping in business. Good bookkeeping will have a positive impact on business and make it easier for business owners to manage and view financial data anytime and from anywhere. The Bim Collection Convection is one of the small and medium enterprises (UKM) in Tangerang City that continues to grow. Along with the wider range of relations and sales, bookkeeping activities at the Bim Collection Convection are of course also increasing and complex. In addition, business owners no longer hold bookkeeping directly, so technological support is needed so that Bim Collection Convection business owners can continue to monitor bookkeeping reports even when they are not at the Convection location. The design of this bookkeeping information system aims to create a sales data management system at the Bim Collection Convection that suits the needs of these SMEs. The method used to design the system is the object oriented analysis and design (OOAD) method which can make the system more dynamic with a high level of reusability.